2020
DOI: 10.1002/sim.8722
|View full text |Cite
|
Sign up to set email alerts
|

Multiply robust estimation of causal quantile treatment effects

Abstract: In causal inference, often the interest lies in the estimation of the average causal effect. Other quantities such as the quantile treatment effect may be of interest as well. In this article, we propose a multiply robust method for estimating the marginal quantiles of potential outcomes by achieving mean balance in (a) the propensity score, and (b) the conditional distributions of potential outcomes. An empirical likelihood or entropy measure approach can be utilized for estimation instead of inverse probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…In this section, we apply our data fusion method to evaluate the causal effect of smoking during pregnancy on birth weight (Abrevaya, 2001;Almond et al, 2005;Xie et al, 2020). Based on the Natality Data Set published by National Center for Health Statistics, Almond et al (2005) showed that births of low-birthweight babies result in both economic costs for society and the children themselves.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we apply our data fusion method to evaluate the causal effect of smoking during pregnancy on birth weight (Abrevaya, 2001;Almond et al, 2005;Xie et al, 2020). Based on the Natality Data Set published by National Center for Health Statistics, Almond et al (2005) showed that births of low-birthweight babies result in both economic costs for society and the children themselves.…”
Section: Applicationmentioning
confidence: 99%
“…To illustrate the validity of our data fusion method, we construct the main dataset by including only the basic confounders: mother's marital status, mother's race (either black or white), gender the infant, mother's age, mother's education and the number of prenatal visits. These five confounders are used as full confounders to evaluate the 0.5th QTE inXie et al (2020). However, there are additional key confounders not included in their analyses: alcohol use during pregnancy, the average number of drinks per week, and adequacy of care.…”
mentioning
confidence: 99%